Serum Phosphate Predicts Early Mortality among Underweight Adults Starting ART in Zambia: A Novel Context for Refeeding Syndrome? - John R. Koethe; Meridith Blevins; Christopher K. Nyirenda; Edmond K. Kabagambe; Janelle M. Chiasera; Bryan E. Shepherd; Isaac Zulu; Douglas C. Heimburger (Journal of Nutrition and Metabolism)
Background. Low body mass index (BMI) at antiretroviral therapy (ART) initiation is associated with early mortality, but the etiology is not well understood. We hypothesized that low pretreatment serum phosphate, a critical cellular metabolism intermediate primarily stored in skeletal muscle, may predict mortality within the first 12 weeks of ART. Methods. We prospectively studied 352 HIV-infected adults initiating ART in Lusaka, Zambia to estimate the odds of death for each 0.1 mmol/L decrease in baseline phosphate after adjusting for established predictors of mortality. Results. The distribution of phosphate values was similar across BMI categories (median value 1.2 mmol/L). Among the 145 participants with BMI <18.5 kg/m2, 28 (19%) died within 12 weeks. Lower pretreatment serum phosphate was associated with increased mortality (odds ratio (OR) 1.24 per 0.1 mmol/L decrement, 95% CI: 1.05 to 1.47; P=0.01) after adjusting for sex, age, and CD4+ lymphocyte count. A similar relationship was not observed among participants with BMI ≥18.5 kg/m2 (OR 0.96, 95% CI: 0.76 to 1.21; P=0.74). Conclusions. The association of low pretreatment serum phosphate level and early ART mortality among undernourished individuals may represent a variant of the refeeding syndrome. Further studies of cellular metabolism in this population are needed.